Bioadhesives for musculoskeletal tissue regeneration. (November 2020) - Tarafder, Solaiman; Park, Ga Young; Felix, Jeffrey; Lee, Chang H.
Abstract: Natural or synthetic materials designed to adhere to biological components, bioadhesives, have received significant attention in clinics and surgeries. As a result, there are several commercially available, FDA-approved bioadhesives used for skin wound closure, hemostasis, and sealing tissue gaps or cracks in soft tissues. Recently, the application of bioadhesives has been expanded to various areas including musculoskeletal tissue engineering and regenerative medicine. The instant establishment of a strong adhesion force on tissue surfaces has shown potential to augment repair of connective tissues. Bioadhesives have also been applied to secure tissue grafts to host bodies and to fill or seal gaps in musculoskeletal tissues caused by injuries or degenerative diseases. In addition, the injectability equipped with the instant adhesion formation may provide the great potential of bioadhesives as vehicles for localized delivery of cells, growth factors, and small molecules to facilitate tissue healing and regeneration. This review covers recent research progress in bioadhesives as focused on their applications in musculoskeletal tissue repair and regeneration. We also discuss the advantages and outstanding challenges of bioadhesives, as well as the future perspective toward regeneration of connective tissues with high mechanical demand. Graphical abstract: Image, graphical abstract